Voila!1 teacher resource book: jacaranda interactive language - Papadima-Sophocleous, Salomi (My University, 2004)
Voila! textbooks are designed as self-contained spreads with high-impact stimulus material, dialogues, language tips, key vocabulary and speaking and listening activities. The books also feature a wide variety of text types, and one of the most comprehensive dictionary and grammar sections ever provided in a French textbook.
Keywords: French language; Textbook for foreign speakers